The incidence of tuberculosis in adolescents in the context of proposed TB vaccine trials - Mahomed, Hassan (Department of Public Health and Family Medicine, 2014)
[Background] Tuberculosis (TB) is a significant global health problem and the development of new TB vaccines is one strategy proposed to address this scourge. Adolescents are a potential target group for new TB vaccines. Limited data are available in the scientific literature on the epidemiology of TB in adolescents. This thesis aimed to add substantial data on adolescent TB epidemiology through a cohort study of TB infection and disease in adolescents in a high burden setting. Such data will support clinical trials of new TB vaccines in adolescents but the knowledge gained will also be of value for TB Control Programmes. [Methods] Adolescents aged 12-18 years were recruited from 11 high schools in the rural town of Worcester and surrounding areas of the Western Cape Province of South Africa. They were screened at baseline for latent TB infection using both the tuberculin skin test (TST) and an interferon gamma release assay, the QuantiFERON® TB Gold (in-tube) assay (QFT). They were also screened for TB disease using an algorithm composed of a set of screening tests. They were followed up for at least two years for incident TB and the predictive value of the baseline TST and QFT for incident TB disease was compared. Demographic, socio-economic and clinical predictive factors for latent TB infection prevalence at enrolment and for incident TB disease during follow up were determined. A survey of attitudes to participation in TB vaccine clinical trials in a subset of adolescents from these schools was also conducted. Both studies had ethics approval. Standard scientific statistical techniques were used to analyse the data. [Results] Fifty eight percent (6363) of the target population of 10,492 adolescents were recruited into the main cohort study. A prevalence of latent TB infection amongst the study participants at enrolment of 55% (TST) and 51% (QFT) was found. Predictive factors for latent infection were: being of black or mixed race origin compared to being of white or indian origin, older age (>15 years), previous household TB contact, low parental income and low education status of the parents. The TST and QFT were found to have good agreement (% agreement 84.8%, kappa [κ] = 0.70, 95%CI 0.68–0.71) in contrast to certain studies in other settings. A baseline prevalence of TB disease of 3/1000 was found in adolescents. While the TST and QFT were sensitive predictors of the presence of TB disease, none of the screening tests evaluated (TB related symptoms, recent household contact, TST or QFT) had high positive predictive values (all less than 2%) making these tests impractical for routine use. Given the imperative for screening in TB vaccine trials, these data are important for deciding on choice of screening tests in a clinical trial setting. Both the TST and QFT were found to be predictive of the onset of TB and were equally predictive. An incidence of bacteriologically confirmed active TB of 0.45/100 (95% confidence interval 0.29-0.72) person years (pyrs) was found in this cohort. Using different definitions of active TB, the rate varied from 0.31-0.59/ 100 pyrs. Risk factors gleaned at baseline that were predictive of the onset of TB disease were: being of black or mixed race origin, maternal education of primary school or less or unknown, evidence of latent infection (positive TST or QFT) and absence of a BCG scar. Knowledge of TB was fair amongst adolescents but willingness to participate in TB vaccine trials varied depending on the procedures involved. [Limitations] Important limitations were as follows. The data presented are likely to underestimate the true prevalence and incidence of TB amongst adolescents in general since adolescents not at school are likely to have higher rates of TB than those attending school. On the other hand TB rates amongst those recruited are likely to have been higher than those not agreeing to participate since participation rates were higher in poorer schools than in more affluent schools. Chest radiographs as a screening tool for TB could not be evaluated because this method of screening was excluded for logistical reasons. The number of TB cases is likely to have been underestimated since smear screening was the main method of case detection and smear negative culture positive TB cases would have been missed. [Application of results] A range of data was obtained through these analyses which will be very useful for planning TB vaccine trials in adolescents and also for TB Control Programmes. Since data were collected in a high TB burden setting, the findings are mainly generalisable to such settings rather than low burden settings. Nevertheless, efficacy trials of new TB vaccines are likely to be carried out in high TB burden settings making these results highly relevant to TB vaccine efficacy trial planning. Policy with respect to the use of interferon gamma release assays will be informed by this data given that it is a relatively new diagnostic modality. Knowledge of the baseline prevalence of TB disease and the utility of different screening tools amongst healthy adolescents would help the design and costing of screening approaches to be used in TB vaccine clinical trials which include adolescents. The data on the prevalence of latent TB infection will assist with the selection of TB vaccine candidates for this target group will be of value given that certain vaccines are designed to target those with latent infection. These data will also support planning where latent TB infection is an exclusion criterion such as in safety trials. TB incidence rates can be used to plan samples sizes for efficacy trials. The comparison of the TST and QFT with respect to prevalence of latent TB infection and predictive value for TB disease provide evidence for policies on the use of these tools in clinical trials and for TB Control Programmes in high burden settings. The fact that these measures showed good agreement and were equally predictive of the onset of TB disease, suggest that the QFT need not replace the TST in current routine practice. However, the two tests may be used interchangeably to equal effect. The knowledge and attitudes of adolescents towards participation in TB vaccine trials provides some guidance with respect to what to expect when approaching this group for recruitment purposes. In summary, the prevalence of latent TB infection, the prevalence and incidence of TB disease and predictive factors for latent infection and disease as well as the knowledge and attitudes of adolescents towards participating in TB vaccine trials are described in this thesis. The application of these results to TB vaccines trials and potential value in TB Control Programmes is discussed.